Štiriletno spremljanje bolnikov po goniotrepanaciji - Hudovernik, Mojca (Zdravniški vestnik, 2002)
Background. To present the success of goniotrepanation in patients with glaucoma 4 years after surgery. Methods. We performed follow-up of 32 patients (50 eyes), who had undergone Fronimopoulus goniotrepanation without use of antimetabolites in our department because of poorly controlled primary open-angle or angle-closure glaucoma and pseudoexfoliative glaucoma between January 1995 and May 1996. The success of operation was assessed 4 years after operation by evaluating the stability of the visual field, stability of the optic nerve head changes and values of the intraocular pressure (IOP) lower than 21 mm Hg. Results. Mean preoperative IOP was 27 mm Hg, one year postoperatively 15 mm Hg and 4 years after the surgery 14 mm Hg (mean drop of IOP was 48%). 1 year after surgery IOP was lower than 21 mm Hg without treatment in 37 eyes (74%) and with additional topical treatment in 12 eyes (24%). After 4 years additional topical treatment was necessary in 54% eyes. Only in 2 patients (4%) revision soon after surgery was performed (because of Tenon's cyst in one case and hypotony in the other). In 1 eye (2%) intraoperative subhoroidal expulsive hemorrhage occurred. In 19 eyes (39%) catarct developed 4 years after surgery. The success of surgery after 4 years was 94%; in 22 eyes (44%) without treatment, in 25 eyes (50%) with additional topical treatment and in 2 eyes (4%) additional surgery was needed. Conclusions. Goniotrepanation without use of antimetabolites can be effective treatment for patients with pseudoexfoliative glaucoma and open-angle glaucoma.
Keywords: Filtering surgery; Filtracijska operacija; Glaucoma; Glavkom; kirurško zdravljenje; Očesni živec; oftalmologija; Optic nerve; Vidna polja; vidni živec; Visual fields